Analysis of the Cochrane Review: Antibiotics for Acute Otitis Media in Children. Cochrane Database Syst Rev. 2013;1:CD000219. - Pinto, Sara (2013)
Acute otitis media is one of the most common infections in children and one of the leading causes for antibiotic prescription. In this paper, we assess and comment the Cochrane systematic review 'Antibiotics for acute otitis media in children', which aimed at assessing the efficacy and safety of antibiotics for acute otitis media in children and identifying subgroups of children who might benefit more than others from antibiotic treatment. This review showed spontaneous resolution of acute otitis media in most children (82%) and a favorable but modest effect of antibiotics, namely in pain control (number needed to treat to benefit: 20), reduction of tympanic membrane perforations and reduction of contralateral acute otitis media. Adverse effects such as vomiting, diarrhea or rash were more common in the antibiotic group (number needed to treat to harm: 14). Thus, for most children, an expectant observational approach during 48-72h without immediate antibiotic prescription seems justified. An additional meta-analysis found that antibiotics appear to be most useful in children with both acute otitis media and otorrhoea and children under two years of age with bilateral acute otitis media.